Asymmetric Synthesis of C1-Chiral THIQs with Imines in Isoquinoline Rings - Li, Dan; Chen, Xiaochao; Gao, Wei (Synthesis, 2020)
Tetrahydroisoquinoline (THIQ) scaffolds are important structural units that widely exist in a variety of natural alkaloids and synthetic analogues. Asymmetric synthesis of C1-chiral THIQ is of particular importance due to its significant pharmaceutical, agrochemical, and other biological activities, and the usually distinct bioactivities exhibited by the two enantiomers. In this review, we highlight the significant advances achieved in this field, present recent asymmetric synthesis with imines in isoquinoline rings ordered according to the sequence of various substrate types. New strategies could be inspired and more types of substrates need further development.1 Introduction2 Catalytic Asymmetric Reaction of Dihydroisoquinolines2.1 Asymmetric Reactions of 3,4-Dihydroisoquinolines2.2 Asymmetric Reactions of Dihydroisoquinolinium Salts2.3 Asymmetric Reactions of C,N-Cyclic N′-Acyl Azomethine Imines2.3.1 NED [3+2] Cycloaddition of C,N-Cyclic N′-Acyl Azomethine Imines2.3.2 IED [3+2] Cycloaddition of C,N-Cyclic N′-Acyl Azomethine Imines2.3.3 [3+3] Cycloaddition of C,N-Cyclic N′-Acyl Azomethine Imines2.3.4 [4+3] Cycloaddition of C,N-Cyclic N′-Acyl Azomethine Imines2.3.5 Asymmetric Addition Reactions to C,N-Cyclic N′-Acyl Azomethine Imines2.4 Asymmetric Reactions of C,N-Cyclic Nitrones3 Catalytic Asymmetric Mannich Reactions of Isoquinolines4 Conclusions and Perspectives
Keywords: asymmetric catalysis; imines; tetrahydroisoquinoline; dihydroisoquinoline; cyclization; addition